Understanding the underuse: Barriers to vacuum-assisted birth among clinicians in Tanzania: An exploratory qualitative study - Lydia S. Massae; Rashidi Heri Kiangi; Victor Zeno Chikwala; Ally Abdul Lyimo; Stella Emmanuel Mushy; Lilian Teddy Mselle (PLoS ONE, 2026)
Background Vacuum-assisted birth (VAB) is a critical obstetric intervention for saving the lives of the mothers and newborns, particularly in cases of prolonged second-stage labor, maternal exhaustion, or fetal distress. Despite its proven benefits, VAB remains underutilized, contributing to an increased rate of unnecessary cesarean sections, some of which could be avoided with timely vacuum extraction. This study aimed to explore the barriers to the use of VAB among clinicians at a tertiary hospital in Tanzania. Materials and Methods An exploratory qualitative study using in-depth interviews (IDIs) was employed. Twelve clinicians with relevant experience in vacuum-assisted birth were recruited purposively into the study. A semi-structured IDI guide was used to facilitate the interviews. Data were analyzed inductively using thematic analysis to identify key patterns and categories related to barriers in the use of VAB. Results Organizational and individual barriers were identified as key challenges to the use of VAB. Organizational barriers included insufficient availability of VAB equipment, ineffectiveness of the available devices, and poor team dynamics that hindered collaborative decision-making regarding VAB use. Individual barriers centered on clinicians’ apprehension about potential adverse outcomes, along with limited skills and practical experience in performing VAB procedures. Conclusion The utilization of VAB by clinicians is hindered by both organizational and individual barriers. Addressing these challenges through improved availability of functional equipment, enhanced training to build clinicians’ skills, and improving working conditions has the potential to increase the use of VAB. Strengthening these areas could help reduce the rate of unnecessary caesarean deliveries.